2018
DOI: 10.15171/ijer.2018.12
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Urinary Tract Infection and Associated Effective Factors During Pregnancy in Shahrekord, Iran

Abstract: Background and aims: This study was conducted to determine the prevalence of urinary tract infection (UTI) in the pregnant women and the associated risk factors in Shahrekord, Iran. Methods: In this cross-sectional study, 832 pregnant women were examined up to 26 to 30 weeks of pregnancy and their UTIs were studied. The required information was collected by examining the health records of pregnant women and completion of the data registration forms. All statistical analyses were performed in SPSS 23.0 using ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Studies have revealed that antibiotic regimens have not shown any decrease in these complications and have imposed a huge financial burden on society. 12 Antibiotic resistance occurs when bacteria have or develop the ability to circumvent the mechanism, which drugs use against them. 13 The resistance of uropathogenic bacteria against antimicrobials is rising globally over time.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed that antibiotic regimens have not shown any decrease in these complications and have imposed a huge financial burden on society. 12 Antibiotic resistance occurs when bacteria have or develop the ability to circumvent the mechanism, which drugs use against them. 13 The resistance of uropathogenic bacteria against antimicrobials is rising globally over time.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that 25% of women get urinary tract infections at least once in their lifetime [ 3 ] [ 4 ]. The prevalence rate of UTI in pregnant women is 7.2–10.4%, and approximately 20–40% of pregnant women with UTI will develop symptomatic UTI if left untreated [ 5 ]. There is evidence that UTI is the main cause of adverse maternal outcomes and obstetrical hospitalization during pregnancy.…”
Section: Introductionmentioning
confidence: 99%